2021
DOI: 10.3390/toxics9090228
|View full text |Cite
|
Sign up to set email alerts
|

Insecticide Exposure and Risk of Asthmatic Symptoms: A Systematic Review and Meta-Analysis

Abstract: Background: The incidence of respiratory disease is increasing. In relation to this, in addition to infection, factors associated with working with chemical insecticides are a cause for concern. Some of the chemicals involved have been shown to affect the respiratory system, and consequentially workers are at increased risk of conditions such as asthma. However, medical opinion around this area is still controversial; therefore, the objective of this study is to investigate the association between exposure to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…Exposure to these chemicals can cause both acute and chronic health consequences (4). Several studies have shown that exposure to OP was associated with chronic diseases such as asthma, rheumatoid arthritis, cancers, Alzheimer's disease, Parkinson's disease, and cognitive impairment (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to these chemicals can cause both acute and chronic health consequences (4). Several studies have shown that exposure to OP was associated with chronic diseases such as asthma, rheumatoid arthritis, cancers, Alzheimer's disease, Parkinson's disease, and cognitive impairment (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…As regards chronic health effects, the evidence is inconsistent, and the mechanisms involved are unclear (7,8). In several human studies, pesticides have been shown to be related to chronic adverse effects on the immune, neurological, respiratory, endocrine, and reproductive systems (7,(10)(11)(12)(13)(14)(15)(16). Symptoms indicating neurobehavioral, motor, and sensory dysfunction, have been reviewed in some symptom prevalence studies (11,(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…Acute poisoning is caused by a single exposure to a high dosage of a pesticide, while chronic conditions are adverse health effects resulting from long-term exposure to pesticides [ 12 , 13 ]. Long term exposure to pesticides can disrupt organ functions such as those in the nervous system, endocrine system, respiratory system, reproductive system, kidney system, cardiovascular system, and immune system, resulting in conditions such as cancer, Parkinson’s disease, Alzheimer’s disease, multiple sclerosis, diabetes, coronary heart disease, chronic kidney disease, respiratory diseases, autoimmune diseases, and systemic lupus erythematosus [ 6 , 14 , 15 , 16 ]. RA is a major immune system disease, according to early studies suggesting that pesticides damage humans’ immune system.…”
Section: Introductionmentioning
confidence: 99%